Time-domain identification of moving load on beam type bridges considering interval uncertainty in finite element model. (15th May 2023) - He, Wen-Yu; Li, Yi-Lin; Yi, Jing-Xian; Ren, Wei-Xin
Abstract: Accurate identification of moving load is one of the main tasks in the field of bridge health monitoring. Due to the uncertainty in practical bridge, moving load identified via deterministic method is bound to be inconsistent with reality. As statistical information on the uncertain parameters is usually limited for actual bridges, this paper proposes a time-domain moving load identification method considering the uncertainty in the finite element model. Firstly, the moving load identification is divided into nominal value and interval radius identification. Then the deterministic methods based on shape function and second-order interval analysis are presented to identify the nominal value and interval radius, respectively. Finally, the effectiveness and superiority of the proposed method are verified through numerical and experimental examples, and the influence of the measurement point number, measurement noise, and vehicle velocity is investigated. The outcomes indicate that the results obtained by the deterministic method may deviate seriously from the actual one, and the calculation efficiency can be enhanced markedly compared with the probability method. The identification accuracy of the proposed method is higher than that of the first-order method at the same computational cost.